Bibliometric Analysis of The Use of Science Learning Media In Elementary Schools During A Decade - Anggun Taruna Puspitasari; Wahono Widodo; Dian Permatasari Kusuma Dayu (UNIVERSITAS PGRI MADIUN, 2024)
This research uses a bibliometric approach to examine how science learning media have been used in elementary schools over the last ten years. The data source used is Dimension AI, with the keywords